Enhancing Student Creativity Through Plastic Waste Integration in Visual Art Education - Abdullah, Dewi Astuti; Alimuddin, Alimuddin; Mukaddas, Baetal (Journal of Innovation and Research in Primary Education, 2025)
Conventional art education in Indonesian secondary schools often limits creative development through teacher-centered approaches and reliance on traditional materials, while plastic waste accumulation presents both environmental challenges and educational opportunities. This study examined how plastic waste integration in visual art education enhances creativity among seventh-grade students at SMP Negeri 6 Kota Ternate. A Classroom Action Research design following the Kemmis and McTaggart model was implemented over two cycles with 32 students. Data were collected through systematic observations, semi-structured interviews, reflective journals, and documentation of artistic products. Creativity assessment employed a validated rubric evaluating originality, flexibility, elaboration, fluency, and risk-taking dimensions. Overall creativity indices increased substantially from 54.25% (pre-cycle) to 87.00% (Cycle II), representing a 32.75 percentage point improvement. All creativity dimensions demonstrated progressive enhancement, with particularly pronounced gains in risk-taking (33%) and elaboration (36%). Students produced increasingly sophisticated two- and three-dimensional artworks while developing collaborative competencies and environmental consciousness. Interview data revealed transformed perceptions of waste materials and spontaneous stewardship behaviors. Plastic waste-based art education effectively cultivates creative capacity while simultaneously fostering environmental awareness and 21st-century competencies. This approach offers a viable, cost-effective pedagogical model for resource-constrained schools, transforming environmental challenges into meaningful learning opportunities that develop creative, environmentally responsible citizens.